Radial line slot array of low radar cross section for target detection and radar stealth in missile-borne sensing systems - Hei, Yanlin (2024)
This article presents a high gain and low radar cross Section (RCS) antenna with low profile for missile-borne sensing systems based on circularly polarized (CP) radial line slot array (RLSA). The RCS reduction of RLSA is studied for the first time by loading chessboard-Arranged polarization conversion metasurface (PCM). Due to the dense and spiral arrangement of slots in RLSA, an integrated design of the radiating slot and periodic PCM unit is challenging. For RCS reduction at frequencies lower than the RLSA's operating frequency, a PCM of high transmissivity is loaded onto the RLSA with an air gap. Wideband RCS reduction is achieved, while its influence on RLSA's radiation performance is negligible. For RCS reduction at high frequencies, the PCM is directly attached on the RLSA to achieve a low profile for the entire antenna system. Under this arrangement, the mutual coupling between PCM units and RLSA's radiating slots is much stronger leading to degradation in RLSA's radiation performance. Hence, a miniaturized PCM is employed to preserve the radiation performance, while the coupling effect is analyzed and quantified into the array design. Two CP RLSA prototypes are fabricated and measured, with a diameter of 9.6 and profiles of 0.18 0.60 at the center frequency of 10 GHz. The peak gain of these two RLSAs is 27.4 dBic and 27.6 dBic, which is reduced by 0.45 dB/0.27 dB compared with the RLSA without PCM. The bandwidth of at least 10-dB RCS reduction is from 13.2 to 24.6 GHz for the high-frequency band and from 3.4 to 7.4 GHz for the low-frequency band. The measured results are in good agreement with simulated ones.